Beneficiation of Ferruginous Manganese Ore of Um Bogma Locality, Sinai: Comparison Between Conventional Reduction Roasting Techniques and Microwave Technology (Rudarsko-geološko-naftni zbornik, 2024)
The increasing demand for high-grade manganese ores in various industries has led to a growing necessity to enhance the quality of lower-grade manganese ores with time. A representative manganese ore was collected from Um Bogma, Sinai, Egypt, and subjected to various characterization methods including X-ray diffraction (XRD), X-ray fluorescence (XRF) and ore microscopy. XRF analysis revealed a low Mn/Fe ratio of 2.81 (as elements), indicating a low ore grade. For suitability in Mn alloy production at the Sinai Manganese Company (SMC) plant in Abu Zenimah, southeast of Sinai, Egypt, this ratio should ideally exceed 5. Additionally, XRD and ore microscopy identified the mineralogical composition of the ore as pyrolusite, hematite, and manganite, with manganese patches embedded in a ferruginous groundmass at the textural scale. Three different reduction roasting techniques were evaluated, involving conventional heating in a furnace utilizing either CO – CO2 or charcoal as reducing agents, alongside reduction roasting with charcoal utilizing microwave technology. Following each technique, magnetic separation was employed, resulting in the production of high-grade manganese concentrates exhibiting high Mn/Fe ratios ranging from 19.8 to 27.45 and substantial Mn recovery rates ranging from 93.86% to 96.76%.